NEOPOGANISM AS A POSTCOLONIAL ISSUE. THE POLISH CONTEXT - Nakoneczny, Tomasz (Porównania, 2019)
Neopaganism is usually perceived as a marginal phenomenon in terms of the scale of social impact. It not only affects the attractiveness of its practices, but also the question of the load-bearing capacity of the world-outlooks exhibited in it. The article attempts to show neopaganism in a broader historical and cultural perspective, taking into account such general issues as cultural identity or memory culture. The author asks the question whether neo-paganism, with its marginality and utopianism, can be considered as a phenomenon inherent in postcolonial (post-dependence) problems. He believes that in the case of countries such as Poland, neopagan constructivism can be treated as a sensible attempt to broaden the base of symbolic references for reflection about its own location on the center-periphery axis.